In Between Realities : German Society, Culture and the Media Entrapped in Hegelian Dialectic Thinking - Langegger Ramos, Andreas (fi=Turun yliopisto|en=University of Turku|, 2017)
Whenever we speak about the traditional press we immediately think about it as the “Fourth Estate” in whom “we” the “public” trust to call out injustices holding thus our governments accountable for their actions. We have thus come to regard the media as our own insurance policy to protect us against government abuses. However, should the press fail to live up to its perceived duty as “protector of the public against the state”, criticism tends to follow suit coming in different shapes and sizes, as can be observed in the case of Der Spiegel’s coverage of the “crises” in Ukraine. Ironically, most of the criticism often tends to emphasize in such scenarios that the media is either ineffective in its role, incompetent or simply “broken”. Therefore, this research has taken it upon itself to ask the opposite question of anyone claiming the media would be ineffective. In fact, what if the media is doing precisely what it is supposed to do? More importantly, what if the media does what it does so well because we have completely neglected to question all our underlying assumptions and believes about journalism, society and our culture at large? The fact that we have been brought up to regard the press as the “Fourth Estate” and to place our unquestionable trust in it, does not mean that the media has ever had the function we have been told that it has or that the press ever deserved our trust to begin with. The problem with most of the existing research, however valuable, is that it has fallen prey to the analysis of the symptoms that have a stranglehold over society and not their respective root causes. Therefore, in almost all of the cases either, capitalism, communism, fascism, democracy, politicians, lobbyists, oligarchs and /or other influential actors or forms of governance are being held responsible for what society is currently undergoing. What makes this illusion perfect is the fact that there exists a seemingly “wide” range of different publications ranging from the far left to the far right and everything in between. These publications criticize one another or their respective political actors making us thus believe in the existence of the “Fourth Estate”. Yet, after each election everything stays the same. Therefore, this research redirects the focus of media studies on the very specific framework that allows all of the above mentioned actors, entities and forms of governance to function the way they do. It is the interconnection between these actors, entities and society within a given framework and their connection to that very same framework itself, that really merits our attention. Because only by developing an understanding of what makes up the fabric of that very communication framework or environment within which different actors try to manipulate reality, or communicate their own version of it to others, will we finally be able to actively take part in creating our own reality. By applying Schmidt’s definition of culture, Halbwach’s (1985) concept of collective memory and adapting Carvalho’s (2008) method of CDA to analyze social structures, entities and actors, this study has shown that the responsibility to question, research and believe any information we are presented with lies with each and every one of us. The media is thus neither lying nor telling the truth. It is simply the transcreator of another reality in between realities within the framework of an ever globalizing world.